SYNDROMAL COMORBIDITY IN PATIENTS WITH NON-CHEMICAL ADDICTION - Mozgova, T.P.; Skrypnikov, A.M.; Vyun, V.V.; Asieieva, Y.О.; Leshchyna, I.V.; Kozhyn, M.I.; Khaustov, M.M. (World of Medicine and Biology, 2021)
The paper presents the results of the study of the comorbid pathology characteristics in conditions of distress in patients with non-chemical addiction. 76 male Internally displaced persons were examined who sought psychiatric help due to the presence of polymorphic symptoms, the main manifestations of which were affective disorders with panic attacks, sleep disturbances and suicidal thoughts. A four-dimensional questionnaire to assess distress, depression, anxiety, and somatization (The Four-Dimensional Symptom Questionnaire – 4DSQ) was used. A high level of depression, anxiety and somatization in patients with non-chemical addiction does not depend on the severity of distress; the effect of distress is a highly pathogenic factor for patients with non-chemical addiction, which acts as a trigger. In the structure of clinical manifestations, depressive dominates the degree of severity and prevalence and anxiety disorders, which augment the appearance of somatic symptoms, cause dysfunction of the autonomic nervous system and determine the abundance and diversity of somatic pathology.
Keywords: male adolescents and juvenile; non-chemical addictions; comorbid pathology